STUDI ATAS KONSEP GENDER DALAM ISLAM - Muhamad Basyrul Muvid muvid (Pusat Studi Gender dan Anak, IAIN Palu, 2022)
Gender has become a hotly debated topic in this millennial era by people who have created many protest movements, one of which is the